Binge Eating Disorder in the Pre And Post-Operative of Bariatric Surgery (Research, Society and Development, 2020)
Introduction: Obesity is a chronic disorder related to excess weight, which affects social and occupational functioning. Among the psychopathologies that can trigger the onset of obesity, there is Binge Eating Disorder. The high prevalence of the disorder in these patients before and after the surgical procedure can be harmful to the effectiveness of the treatment. Objective: This study aims to evaluate the prevalence of Binge Eating Disorder in the pre and postoperative period of bariatric surgery, correlating with the sociodemographic variables. Method: This is a cross-sectional observational study, in which the Binge Eating Scale and a socio-demographic questionnaire were applied to patients at the “Instituto do Aparelho Digestivo”, in Campo Grande-MS. The sample consisted of 34 patients 6 months after the procedure, and 59 individuals undergoing preoperative follow-up. Results: Regarding the presence of Periodic Eating Compulsion Disorder in the preoperative period, a prevalence of 30.5% was observed over the studied population. Regarding the prevalence 6 months after the surgery, 35.2% of the patients in the sample had results compatible with binge eating, 50% of whom had severe Binge Eating Disorder. Conclusion: The prevalence of Binge Eating Disorder is high before and after bariatric surgery in morbidly obese individuals, especially in the female public aged between 30 and 40 years, since in other sociodemographic variables there was no relevant statistical association. This denotes the need for a comprehensive psychic assessment of morbidly obese patients undergoing this surgical procedure.